Drinking Frequency but not Years may be Associated with Lower Urinary Tract Symptoms: Result from a Large Cross-Sectional Survey in Chinese Men - Lu Z; Wu C; Zhang J; Ye Y; Zhang Z; Liao M; Huang L; Tian J; Tan A; Mo Z (Dove Medical Press, 2020)
Zheng Lu,1,* Chunlei Wu,2,3,* Jiange Zhang,2,4,* Yu Ye,2,5 Zhifu Zhang,2,6 Ming Liao,2 Lin Huang,2 Jiarong Tian,2 Aihua Tan,2 Zengnan Mo1,2 1Department of Urology, First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 2Center for Genomic and Personalized Medicine, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 3Urology Department, First Affiliated Hospital of Xinxiang Medical University, Weihui City, Henan Province, People’s Republic of China; 4Department of Urology, Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 5Emergency Department, Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 6Department of Urology, Minzu Hospital of Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zengnan MoDepartment of Urology, First Affiliated Hospital of Guangxi Medical University, 6 Shuangyong Road, Nanning 530021, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaTel/ Fax +86 0771-5353342Email zengnanmo@hotmail.comObjective: To evaluate the effect of the drinking frequency and years on lower urinary tract symptoms (LUTS) in a large Chinese male population.Methods: The current data were obtained from a consecutive series of 3,229 men aged 18– 79 who participated in a routine physical examination in Fangchenggang First People’s Hospital, Guangxi, China. During a face-to-face interview, the detailed demographic variables about alcohol consumption, potential confounding factors were collected. LUTS were assessed by International Prostate Symptom Score (IPSS) and defined as total LUTS, irritative (IRR) and obstructive (OBS) symptoms, respectively. Multivariate logistic regression analysis was used to evaluate the risk of total LUTS, IRR and OBS symptoms affected by alcohol consumption.Results: The prevalence of moderate to severe LUTS was 8.3% and apparently increased with age (P< 0.001). A significant distribution presented in age, alcohol consumption, BMI, cigarette smoking, education attainment and hypertension among different strata of LUTS severity (P< 0.05). Men who drank 1– 2 times per week were less likely to have OBS symptoms (OR=0.45, 95% CI=0.29– 0.70) regardless of age (OR=0.52, 95% CI=0.33– 0.82) or multivariate adjusted (OR=0.52, 95% CI=0.33– 0.83). Nevertheless, we did not observe a significant negative or positive association presented between drinking years and the risk of total LUTS, OBS and IRR symptoms.Conclusion: The current results imply that moderate drinking frequency may be protective against LUTS, and drinking years did not relate to worsening or improving LUTS.Keywords: observational study, alcohol consumption, urinary tract, epidemiology